The Efficacy of Laser Fluorescence to Detect in Vitro Demineralization and Remineralization of Smooth Enamel Surfaces - Diniz, Michele Baffi [UNESP]; Paes Leme, Adriana Franco; Cardoso, Katia de Sousa; Rodrigues, Jonas de Almeida [UNESP]; Loiola Cordeiro, Rita de Cassia [UNESP] (Mary Ann Liebert, Inc., 2009)
Objective: The purpose of this study was to evaluate the efficacy of the laser fluorescence (LF) device in detecting in vitro demineralization and remineralization of smooth surface caries-like lesions. Background Data: The early detection of smooth surface caries-like lesions is important to provide proper management of carious lesions, and allows monitoring of them over time. Also, some authors suggest that LF could be useful in monitoring the caries pathological process. Materials and Methods: Seventy-eight blocks of bovine teeth were obtained, and then submitted to artificial caries lesion induction and to a pH-cycling process. Superficial microhardness (SMH) and laser fluorescence analysis were performed at baseline, after induction of caries-like lesions, and after the pH-cycling regimen to promote remineralization. Results: Friedman's and multiple comparison tests were performed for all variables. SMH analysis showed significant differences (p < 0.05) between baseline (286.77 +/- 1.49 Vickers hardness number [VHN] units), before (38.48 +/- 0.85 VHN), and after remineralization (131.93 +/- 2.63 VHN). Baseline values for LF were extremely low (2.71 +/- 0.05), and a statistically significant difference was observed only after remineralization (3.61 +/- 0.08), as demonstrated by the increase in LF values. Conclusion: The LF device did not show efficacy for monitoring in vitro demineralization and remineralization of smooth enamel surfaces.